Analysis of students' mathematical representation based on levels of mathematical ability - Mutiah Hasanuddin; Sutji Rochaminah; Dasa Ismaimuza; Muhammad Fachri B. Paloloang (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2025)
Mathematical representation is a fundamental skill in mathematics learning, allowing students to express and solve problems through symbolic, verbal, and visual forms. However, students' varying levels of mathematical ability can significantly influence the quality of their representational skills. This study employed a descriptive qualitative method involving three eighth-grade students from SMPN 2 Kasimbar, selected based on their mathematical abilities: high, medium, and low. Data were collected through tests and semi-structured interviews, and analyzed using data condensation, data display, and conclusion drawing techniques. The results indicated that high-ability students could construct and solve systems of linear equations in two variables, although they exhibited some difficulty in interpreting variables accurately. Medium-ability students demonstrated proficiency in formulating equations and performing calculations, with particular strength in verbal and visual representations. In contrast, low-ability students struggled with algebraic operations, often misused variables, and were unable to generate appropriate graphical representations. These findings highlight the significant role of mathematical ability in shaping students' representation skills and underscore the need for teachers to implement more adaptive and differentiated instructional strategies.